A Mammal-Specific Exon of WT1 Is Not Required for Development or Fertility - Natoli, Thomas A. (American Society for Microbiology, 2002)
The WT1 tumor suppressor gene is a zinc finger-containing transcription factor which is required for development of the kidney and gonads. A mammal-specific alternative splicing event within this gene results in the presence or absence of a 17-amino-acid sequence within the WT1 protein. To determine the function of this sequence in vivo, gene targeting was utilized to specifically eliminate the exon encoding this sequence in mice. Mice lacking WT1 exon 5 develop normally. Adult mice lacking this exon are viable and fertile, and females are capable of lactation.